The relationship between physical work environment and employees’ work performance at Digi Store Danga Bay Johor Bahru / Ahmad Nur Aiman Othman - Othman, Ahmad Nur Aiman (2020)
This study attempts to shows the relationship between physical work environment and employee work performance at Digi Store Danga Bay, Johor Bahru. The independent variables used in this research was physical work environments consist of office lighting, office furniture, office noise and office air quality. Meanwhile the dependent variable was employees’ work performances. The problems statement is this research was attempts to identify the factor of physical work environment and employees’ work performance. In addition, to investigate the relationship between physical work environment and employee’s work performance at Digi Store Danga Bay, Johor Bahru. The researcher used the questionnaire to collect the data in this research. Therefore, the questionnaires were distributed to all employees according to the sampling technique choose at Digi Store Danga Bay, Johor Bahru. The respondents that answer the questions was 32 from 34 respondents. This research has shown the result of factors and relationship between physical work environment and employees’ work performance. All the result is using the SPSS software